Tourism Object Development in Samosir Regency, Indonesia - Kariaman Sinaga; Suwardi Lubis; Marlon Sihombing; Ritha F Dalimunthe (Budapest International Research and Critics University, 2018)
Potential tourism objects in an area, especially Samosir Regency, are very diverse, including natural beauty, history, culture that has its own charm. The tourism sector is one of the strategic sectors and the mainstay in Samosir Regency as a locomotive driving the improvement of the community's economy which contributes to the region's original income (PAD). The development of tourism objects in Samosir Regency is adjusted to the potentials of each community-based tourism object. The development of this tourism object is also stipulated by the Decree of the Samosir Regent Number 474 of 2017 concerning the Determination of Criteria and Classification of Tourism Objects in Samosir Regency which is carried out through the pattern of tourism development in ways or methods of work in optimizing the potential possessed. Criteria for tourism objects that have been regulated in tourism development policies can be used as a measure to develop tourism objects in Samosir Regency.